Carbonyl group-assisted 1,3-amine addition to α,β-unsaturated aldehydes - Zhang, Zhenguo (2024)
An unusual 1,3-addition products were obtained when amines were reacted with α,β-unsaturated aldehydes compounds in the presence of iodine and an oxidant. The versatile unsaturated α-amino acetals are highly useful amino acid derivatives and can be converted to a wide variety of synthetically useful building blocks. Various control experiments have shown that the reaction proceeded via a mechanism involving the formation of imine/enamine intermediates followed by a 1,2-amine group migration reaction.